KEWENANGAN MAJELIS KEHORMATAN NOTARIS WILAYAH DALAM MEMBERIKAN PERSETUJUAN TERHADAP PEMANGGILAN NOTARIS OLEH PENEGAK HUKUM - Udi Hermawan; Munsyarif Abdul Chalim (Jurnal Akta, 2017)
Referring to the provision of Article 66 Paragraph (1) of Law Number 2 Year 2014, Assembly Honor Notary is authorized to approve the calling of a Notary by law enforcement. The authority of the Assembly Honor Notary is to replace the authority of the Regional Notary Supervisory Board in the case of giving approval to the calling of a Notary by law enforcement as stated in Article 66 Paragraph (1) of Law Number 30 Year 2004, which has been abolished by the Constitutional Court of the Republic of Indonesia through the Decision of the Constitutional Court of the Republic of Indonesia Number 49 / PUU-X / 2012 because it is contradictory to the 1945 Constitution of the State of the Republic of Indonesia. After the enactment of Law Number 2 Year 2014 the authority is reappeared and delegated to the Assembly Honor Notary. The research is empirical juridical research using primary law material, secondary law material, and tertiary legal material. After all the data collected then arranged systematically then analyzed qualitatively, and presented descriptively.The conclusion of this research is that the exercise of the authority of the Assembly Honor Notary in giving approval to the calling of a Notary by law enforcement has been done accordingly in accordance with the provisions of the prevailing laws and regulations and should continue to run as a safeguard against the Notary. A common obstruction is the difficulty of bringing together members of the Assembly Honor Notary when conducting an examination hearing. Related to that, there must be a commitment from each member of the Assembly Honor Notary to be able to perform his / her duties and obligations as a member of the Assembly Honor Notary.Key Words: Authority, Assembly Honor Notary, Calling a Notary.